Activity and conformation of lysozyme in molecular solvents, protic ionic liquids (PILs) and salt–water systems. Issue 37 (8th September 2016) - Wijaya, Emmy C.; Separovic, Frances; Drummond, Calum J.; Greaves, Tamar L.
Abstract : The role of solvent features on enzyme stability was investigated by comparing the conformation and activity of lysozyme in molecular solvents, PILs and salt solutions. Electrostatic interactions and the solvophobic effect dominated at low and high solvent concentrations, respectively. Abstract : Improving protein stabilisation is important for the further development of many applications in the pharmaceutical, specialty chemical, consumer product and agricultural sectors. However, protein stabilization is highly dependent on the solvent environment and, hence, it is very complex to tailor protein–solvent combinations for stable protein maintenance. Understanding solvent features that govern protein stabilization will enable selection or design of suitable media with favourable solution environments to retain protein native conformation. In this work the structural conformation and activity of lysozyme in 29 solvent systems were investigated to determine the role of various solvent features on the stability of the enzyme. The solvent systems consisted of 19 low molecular weight polar solvents and 4 protic ionic liquids (PILs), both at different water content levels, and 6 aqueous salt solutions. Small angle X-ray scattering, Fourier transform infrared spectroscopy and UV-vis spectroscopy were used to investigate the tertiary and secondary structure of lysozyme along with the corresponding activity in various solvation systems. At low non-aqueous solvent concentrations (high water content), the presence of solvents and salts generally maintained lysozyme in its native structure and enhanced its activity. Due to the presence of a net surface charge on lysozyme, electrostatic interactions in PIL–water systems and salt solutions enhanced lysozyme activity more than the specific hydrogen-bond interactions present in non-ionic molecular solvents. At higher solvent concentrations (lower water content), solvents with a propensity to exhibit the solvophobic effect, analogous to the hydrophobic effect in water, retained lysozyme native conformation and activity. This solvophobic effect was observed particularly for solvents which contained hydroxyl moieties. Preferential solvophobic effects along with bulky chemical structures were postulated to result in less competition with water at the specific hydration layer around the protein, thus reducing protein–solvent interactions and retaining lysozyme's native conformation. The structure–property links established in this study are considered to be applicable to other proteins.